The quality of life of patients with genital warts: a qualitative study - Larsen Helle K; Mortensen Gitte (BMC, 2010)
Abstract Background Genital warts, which are caused by infection with human papillomavirus (HPV), are one of the most common sexually transmitted diseases in Europe. Although genital warts are commonly perceived as a non-serious condition, treatment is often long, of varying effectiveness and the recurrence rate is high. Very few studies have been performed on the personal consequences of genital warts. The aim of this qualitative study, set in Denmark, was to examine the ways in which genital warts may affect patients' quality of life. Methods To obtain an in-depth understanding of patients' perceptions of genital warts, we used qualitative focus-group interviews with five men and five women aged between 18 and 30 years who had genital warts. The interview guide was based on a literature review that identified important issues and questions. The data were analysed using a medical anthropological approach. Results Patients' experiences were related to cultural conceptions of venereal diseases and the respective identities and sexuality of the sexes. The disease had negative psychological and social effects both for men and for women and it affected their sex and love lives, in particular. The psychological burden of the disease was increased by the uncertain timeline and the varying effectiveness of treatment. We identified a need for more patient information about the disease and its psycho-sexual aspects. Conclusions The men and women participating in this study considered their quality of life to be significantly lowered because of genital warts. The experiences described by the participants give insights that may be valuable in treatment and counselling. The quadrivalent HPV vaccine that has now been added to the childhood vaccination programme for girls in Denmark for the prevention of cervical cancer can also prevent 90% of cases of genital warts. Our results suggest that HPV vaccination could considerably reduce the largely unacknowledged psychological and social burden associated with genital warts, in men as well as women.